INFORMATICAL EDUCATION IN THE TECHNOLOGICAL EDUCATION - DUCHOVIČOVÁ, Marcela (Trends in education, 2008)
The background as well as demand of information society accomplished the technological possibilities there are the essence of educational system. This demand increased on claim for utilization of ICT. The introduction of upper presented claims for reconstruction of present system of education including of content of this.
Keywords: technical education; innovations; effectiveness; multimedia teaching aid.